2011
DOI: 10.1016/j.jcin.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up After Fractional Flow Reserve–Guided Treatment Strategy in Patients With an Isolated Proximal Left Anterior Descending Coronary Artery Stenosis

Abstract: Medical treatment of patients with a hemodynamically nonsignificant stenosis (FFR ≥ 0.80) in the proximal LAD is associated with an excellent long-term clinical outcome with survival at 5 years similar to an age- and sex-matched control population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 31 publications
1
55
0
2
Order By: Relevance
“…The use of PCI of intermediate stenosis without evidence of ischemia is frequent in clinical practice, but its benefit is highly debated. When revascularization is based mainly on angiographic guidance, a number of hemodynamically non-significant stenoses will be revascularized [21], and revascularization of non-ischemic lesions is controversial [22][23][24]. A recent analysis in patients with left main coronary disease comparing revascularization with deferred revascularization, suggested a higher incidence of adverse cardiovascular events in both the groups [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PCI of intermediate stenosis without evidence of ischemia is frequent in clinical practice, but its benefit is highly debated. When revascularization is based mainly on angiographic guidance, a number of hemodynamically non-significant stenoses will be revascularized [21], and revascularization of non-ischemic lesions is controversial [22][23][24]. A recent analysis in patients with left main coronary disease comparing revascularization with deferred revascularization, suggested a higher incidence of adverse cardiovascular events in both the groups [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although coronary angiography often underestimates or overestimates the functional severity of a lesion, it is still the standard technique for guiding PCI in patients with multivessel CAD [26]. Coronary pressure-derived FFR is an invasive index used to identify stenosis responsible for reversible ischemia, and is well validated [21,27,28]. An FFR of 0.80 discriminates coronary stenosis responsible for ischemia with an accuracy >90% [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] An FFR value ≤0.75 is almost uniformly associated with signs of ischemia, [4][5][6][7][8][9] whereas an FFR >0.80 is usually associated with the absence of ischemia. Based on numerous randomized trials [2][3][4][5] and registries in most subsets of lesions and patients, the threshold value of 0.80 has been widely accepted to guide clinical decision making.…”
mentioning
confidence: 99%
“…40 A number of other studies also have demonstrated the safety and benefit of deferring the revascularization of lesions that are not physiologically significant based on FFR assessment. [41][42][43] The improved outcomes with FFR-guided PCI in the FAME trial were related to relieving ischemia with revascularization and to minimizing unnecessary revascularization. By achieving a functionally complete revascularization, instead of an anatomically complete one, the benefit of PCI could be maximized while also minimizing the risks of the procedure.…”
Section: Fractional Flow Reservementioning
confidence: 99%